Gereja sebagai Keluarga Allah Bagi Para Mantan Narapidana [The Church as God's Family for Ex-Prisoners] - Yolanda Lase; Lindawati Lindawati (Universitas Pelita Harapan, 2023)
The church, as a representation of God's family, should actively provide support and guidance to individuals who have been released from prison and are capable of reintegration into society. Unfortunately, in reality, many churches fail to demonstrate acceptance towards former inmates, which leads to their isolation and drives them to seek support in less positive environments. This study utilizes a literature review approach, involving the search, selection, and evaluation of published materials like books, academic journals, articles, theses, and prior research reports relevant to the subject. The findings from this method reveal that the church's role as God's family remains largely unfulfilled, especially concerning those individuals labeled as 'ex-convicts.' Hence, it is imperative for the church to rekindle its commitment to embracing, loving, and guiding former prisoners through spiritual and social assistance, recovery and rehabilitation programs, community empowerment initiatives, and by offering hope and forgiveness to those seeking redemptionBAHASA INDONESIA ABSTRACT: Gereja sebagai keluarga Allah harus berperan dalam memberikan dukungan dan bimbingan kepada para mantan narapidana yang sehat setelah mereka dibebaskan dari penjara. Namun, pada kenyataannya, banyak gereja yang tidak menerima kunjungan mantan narapidana, sehingga kehadiran gereja justru mengucilkan mereka dan mendorong mereka untuk mencari dukungan dan bimbingan di lingkungan yang kurang positif. Metode yang digunakan dalam penelitian ini adalah tinjauan pustaka. Metode ini melibatkan pencarian, pemilihan, dan evaluasi literatur yang telah dipublikasikan, seperti buku, jurnal ilmiah, artikel, tesis, dan laporan penelitian terdahulu yang berkaitan dengan topik yang diteliti. Berdasarkan metode ini, diperoleh hasil bahwa peran gereja sebagai keluarga Allah belum sepenuhnya terlaksana, terutama bagi mereka yang dikenal sebagai ekses. Oleh karena itu, gereja perlu menyadarkan kembali bahwa hal tersebut termasuk menerima, mengasihi dan membimbing para mantan melalui pendampingan rohani, pendampingan sosial, pemulihan dan rehabilitasi, pemberdayaan masyarakat, serta memberikan pengharapan dan pengampunan kepada para mantan penyandang disabilitas.